Rational design of non-noble-metal-based alloy catalysts for hydrogen activation: a density functional theory study. Issue 17 (22nd November 2022) - Li, Danyang; Chen, Zhili; Ren, Kui; Zhao, Shuang; Xu, Haoxiang; Cao, Dapeng
ABSTRACT: The alloying of precious metals with non-noble metals in the active components for hydrogen activation during regeneration of the solid acid catalyst in hydrogenation conditions, can reduce the cost of the catalyst and improve the catalytic efficiency of precious metals. However, it lacks a theoretical method to guide the development of non-noble-metal-based alloy catalysts. In this work, the dependence of hydrogen adsorption and dissociation of alloy models on various non-noble-metal bases has been investigated by first-principles calculations. When the surface metal elements are in the same line of periodic table, the adsorption strength of hydrogen on the alloy weakens with the increase of the atomic number of the surface metal element. Importantly, we establish a screening model to make high-throughput predictions for non-noble-metal-based alloy modified with precious metal. This work provides a reasonable design strategy to guide the development of alloy catalysts used in hydrogen activation by identifying specific non-noble-metal bases. GRAPHICAL ABSTRACT: UF0001